Psicoanálisis y Marxismo: una imposibilidad paradigmática - Martínez, Manuel (2022)
The present article approaches the controversy and problematic relation between two of the great theoreticians of modernity, as they are the marxism and the psychoanalysis, who, have been object of numerous efforts historically speaking. It is not tried here to review to such efforts, if not rather to include/understand conceptually its departure assumptions and to establish, in adjustment to these, the viability of a new metatheoretic formulation.